Gaya Kepemimpinan Karismatik: Panglima Jilah Pemimpin Pasukan Merah - Riyant, Petrus (Institutum Theologicum Ioannis Mariae Vianney Surabayanum, 2023)
This paper focuses on the leadership model of Panglima Jilah as the great leader of the (TBBR) in Borneo, Kalimantan. As Panglima Jilah became a symbol struggle for justiceof the Dayak people themselves and at the same time by leading and organizing forty-eight thousand personnel in the Pasukan Merah Bangkule Rajankng organization, Kalimantan. Therefore, the focus of this discussion departs from the author's awareness and love related to the experience and dynamics of a leadership in an organization. As asserted by Wahjosumidjo that leadership is essentially something inherent in a leader. Which something is in the form of certain traits such as personality, ability and capability. Departing from that, it is important that the leadership style of an influential figure in Kalimantan needs to be examined, explored and raised more deeply, both philosophically and from the point of view of modern era leadership management. The methodology used in writing this paper is the literature method with source books on leadership theory and other sources that support writing. In addition, in order to ensure validity and originality, this paper is also accompanied by some results of experiences sharing and dialogue with activists involved in TBBR membership during their one-year pastoral care in St. Joseph Meraban Parish, Diocese of Ketapang.